LEGAL AND JUDICIAL POLICY FOR THE PROTECTION OF URDU LANGUAGE IN STATE OF UTTAR PRADESH IN INDIA - M.Z.M. Nomani, Madiha Tahreem (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Section 2 of the Uttar Pradesh Official Language Act, 1951 provides for the adoption of Hindi as the language to be used for the official purposes in Uttar Pradesh. The state Government amended the Three Language Formula in 1963 which substituted mother tongue of Muslim population. The imperatives of modern education in English language and conservation of script, language, and culture became dexterous for the Urdu speaking population. The Uttar Pradesh Official Language (Amendment) Ordinance, 1982 recognized Urdu for the first time as second language. The express verbis declaration of Urdu as the second official language also reflected in U.P. Official Language (3rd Amendment) Ordinance, 1983 and Uttar Pradesh Official Language (Amendment) Act, 1989. The Urdu speaking populace’s happens to be sizable in state of Uttar Pradesh but the language did not rise proportionately over the last seven decades. The paper analyses the legal and judicial policies for the protection of the Urdu language in the light of the U.P. Hindi Sahitya Sammelan v. State Of U.P. verdicts of the Allahabad High Court and Supreme Court of India.